2009
DOI: 10.1113/expphysiol.2009.048108
|View full text |Cite
|
Sign up to set email alerts
|

Possible contribution of the non‐proteolytic activation of prorenin to the development of insulin resistance in fructose‐fed rats

Abstract: Recent studies have shown that blocking non-proteolytically activated prorenin with a decoy peptide for the handle region of the prorenin prosegment (HRP) inhibits the development of microvascular complications in diabetic animals. In the present study, we investigated whether non-proteolytic activation of prorenin contributes to the development of fructose-induced insulin resistance. Rats were fed a standard diet (n = 10), a 60% high fructose diet (n = 16), or a high fructose diet + HRP (0.1 mg kg −1 day −1 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 29 publications
4
31
1
Order By: Relevance
“…However, in apparent contrast with the above in vitro results on glucose-induced (P)RR upregulation in mesangial cells, HRP (0.2 mg/kg of body weight per day) did not suppress the elevated renal interstitial AngII in diabetic rats, nor normalized the increased (P)RR expression in this model [88]. In fact, the lack of effect of HRP on (P)RR expression appears to be a general phenomenon in in vivo studies applying this drug [76,78,[89][90][91]. AT 1 receptor blockade with valsartan did normalize (P)RR expression, and both HRP and valsartan suppressed the up-regulated TGFβ1 levels in the diabetic rat kidney [92].…”
Section: Kidney and Diabetescontrasting
confidence: 83%
See 1 more Smart Citation
“…However, in apparent contrast with the above in vitro results on glucose-induced (P)RR upregulation in mesangial cells, HRP (0.2 mg/kg of body weight per day) did not suppress the elevated renal interstitial AngII in diabetic rats, nor normalized the increased (P)RR expression in this model [88]. In fact, the lack of effect of HRP on (P)RR expression appears to be a general phenomenon in in vivo studies applying this drug [76,78,[89][90][91]. AT 1 receptor blockade with valsartan did normalize (P)RR expression, and both HRP and valsartan suppressed the up-regulated TGFβ1 levels in the diabetic rat kidney [92].…”
Section: Kidney and Diabetescontrasting
confidence: 83%
“…Moreover, in diabetic SHRsp [stroke-prone SHR (spontaneously hypertensive rats)] on a high-salt diet, the beneficial effects of HRP (0.1 mg/kg of body weight per day) and ACE inhibition on protein excretion and heart weight (but not on renal and cardiac AngII content) were additive [77]. HRP (0.1 mg/kg of body weight per day) also normalized the elevated fasting plasma triacyglycerols (triglycerides), total cholesterol and insulin levels in rats fed high fructose, without affecting the elevated BP in these animals [78]. Taken together, these findings suggest that HRP exerts beneficial effects in a variety of (diabetic) models in an AngIIindependent manner.…”
Section: Kidney and Diabetesmentioning
confidence: 88%
“…MI mice were randomly grouped to be treated with saline or HRP (0.1 mg·kg body wt Ϫ1 ·day Ϫ1 ; GeneDesign, Osaka, Japan) subcutaneously for 4 wk using an osmotic minipump (model 2004 ALZET, CA). The concentration of HRP and the duration of treatment in the present study were chosen based on the previous study of their efficacy (33). Experiments were performed after 4 wk of operation in the following four groups: 1) Sham (n ϭ 10), 2) ShamϩHRP (n ϭ 10), 3) MI (n ϭ 10), and 4) MIϩHRP (n ϭ 10).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these clinical studies suggest that mild insulin resistance can contribute to the exacerbation of HF. A previous study demonstrated that HRP ameliorated glucose intolerance in fructose-fed rats (33). Furthermore, the effect of HRP on insulin resistance was due to normalization of insulin signaling, including serine phosphorylation of Akt and GLUT4 translocation in the skeletal muscle from MI.…”
Section: E509 (Pro)renin Receptor In Insulin Resistance From Hfmentioning
confidence: 99%
See 1 more Smart Citation